Microstructural, physicochemical, thermal, and rheological properties of buckwheat flour treated with high-pressure at selected moisture contents - Ahmed, Jasim; Thomas, Linu; Mulla, Mehrajfatema; Brishti, Fatema Hossain (Academic Press, 2024)
This study investigated the role of water in the high-pressure treatment (300–600 MPa/15 min) of buckwheat (Fagopyrum esculentum) flour and property changes in post-process samples. DSC and XRD measurements demonstrated complete gelatinization of buckwheat starch occurred at 600 MPa. The particle size of flour decreased above 450 MPa. HP-treatment successfully transformed the crystalline A-type structure of hydrated samples into a B-type structure. Dry samples did not gelatinize or exhibit any structural change, even at 600 MPa. The progress of gelatinization and gel rigidity of post-process samples were measured on a rheometer. The thermal transition captured in rheometer and DSC differs significantly. The impact of further heating on the pressurized samples resulted in a significant improvement in their mechanical rigidity. Overall, this study confirmed that an optimum flour-to-water ratio should be maintained during HP treatment to achieve the desired changes in buckwheat flour so that it could be used in food formulation.